Ultrasonic monitoring of friction contacts during shear vibration cycles. (December 2021) - Fantetti, Alfredo; Mariani, Stefano; Pesaresi, Luca; Nowell, David; Cegla, Frederic; Schwingshackl, Christoph
Highlights: Ultrasound is used to monitor non-transparent friction contacts during vibration. Strong ultrasonic signal modulation through the contact interface during vibration. Ultrasonic signal modulation is linked to stick/slip contact state transitions Ultrasonic transmission is shown to decrease with increasing sliding amplitude. Above-identified features enable real-time contact state detection via ultrasound. Abstract: Complex high-value jointed structures such as aero-engines are carefully designed and optimized to prevent failure and maximise their life. In the design process, physically-based numerical models are employed to predict the nonlinear dynamic response of the structure. However, the reliability of these models is limited due to the lack of accurate validation data from metallic contact interfaces subjected to high-frequency vibration cycles. In this study, ultrasonic shear waves are used to characterise metallic contact interfaces during vibration cycles, hence providing new validation data for an understanding of the state of the friction contact. Supported by numerical simulations of wave propagation within the material, a novel experimental method is developed to simultaneously acquire ultrasonic measurements and friction hysteresis loops within the same test on a high-frequency friction rig. Large variability in the ultrasound reflection/transmission is observed within each hysteresis loop and is associated with stick/slip transitions. The measurement results reveal that the ultrasound technique can be used to detect stick and slip states in contact interfaces subjected to high-frequency shear vibration. This is the first observation of this type and paves the way towards real-time monitoring of vibrating contact interfaces in jointed structures, leading to a new physical understanding of the contact states and new validation data needed for improved nonlinear dynamic analyses.